An Analytical Study of the Implications of the Gesture of the Prophet Muhammad (SAW) - Muhammad Bilal Farooqi (Seerat Studies, 2024)
This research explores the significance of nonverbal communication through the gestures of the Prophet Muhammad (SAW) as preserved in Hadith. It highlights the systematic approach taken by the Companions (may Allah be pleased with them) to document these gestures, emphasizing their role in understanding the meanings and implications of the Prophet's teachings. The study aims to establish the communicative and educational value of these gestures and their relevance in contemporary pedagogical practices.